UTILIZATION OF COMPOUNDED FEED AND POULTRY HATCHERY WASTE IN THE DIET OF Clarias gariepinus - AYOOLA, S. O (Nigerian Journal of Fisheries, 2011)
Five isonitrogenous diets (100% compounded feed - control feed), 75% compounded feed and 25% poultry waste, 50% compounded feed and 50% poultry waste, 25% compounded feed and 75% poultry waste and 100% poultry hatchery waste) were formulated . The hatchery waste was sun dried for three days, ground, added to the feed and fed to 150 juveniles of Clarias gariepinus distributed in 15 (high density polyethylene) tanks. Ten specimens were stocked in each of the plastic tanks and fish were fed thrice daily for 12 weeks. The result showed that specimens fed with 75% compounded feed and 25% poultry hatchery waste had the highest mean weight gain (MWG) (22.7g) and specific growth rate (SGR) (45.3%). The second best result was shown in specimens fed with 100% compounded feed with the highest daily rate of growth (DRG) (0.0105), gross efficiency of feed conversion (GEFC) (0.4688), protein efficiency ratio (PER) (0.153) and lowest feed conversion ratio (FCR) (3.657). The poorest result was shown in the specimens fed with 25% compounded feed and 75% poultry hatchery waste recording the least MWG (16.2), SGR (40.3), DRG (0.0073), GEFC (0.0268), PER (0.106) and the highest FCR (5.257). This implies that poultry hatchery waste can best be utilized when formulated with compounded feed at a ratio of 25% to 75%. Therefore, this ratio should be adopted by fish farmers whose intention is profit maximization and reduction in running cost.